Drop-In Group Medical Appointments for Patients with Asthma: A Four-Year Outcomes Study. (16th May 2011) - Liebhaber, Myron; Bannister, Rob; Raffetto, Wendy; Dyer, Zeb
Abstract : Our DIGMA program was established to allow patients time to interact with an allergist, a behaviorist and an asthma educator in a group setting. Weekly meetings targeted patients with chronic asthma. DIGMAs typically last for 90 minute s and include 10 patients per session. Outcome parameters were established to assess the effectiveness of the program over a 4 year time period. Sixty four adult asthmatic patients were enrolled and followed for 4 years. Patients were seen in a group setting in groups of ten. The AQLQ test was administered each year. Spirometry, an analog self assessment scale and the ACT were administered at each visit. Forty two of the 64 patients were followed for a minimum of 3 visits to DIGMA during four years. The average baseline FVC was 85% predicted and remained unchanged. FEV1 was 78% baseline and was 77% at the last determination. Baseline rescue inhaler use was 4 per week compared to 1.5 per week at last visit. ACT scores are 18 at baseline and 19 at last visit. ER claims are 5 at one year prior to enrollment and 2 at the last year of DIGMA. Patient satisfaction improved from 30 to 34 at the last visit. This was an effective, multidisciplinary asthma intervention that focused on behavior. It fulfilled the goals of asthma care as described by the 2007 NAEPP guidelines.